Movement variability in the golf swing - Langdown, B. L.; Bridge, M.; Li, F. X. (Sports Biomechanics, 2012)
Traditionally, golf biomechanics has focused upon achieving consistency in swing kinematics and kinetics, whilst variability was considered to be noise and dysfunctional. There has been a growing argument that variability is an intrinsic aspect of skilled motor performance and plays a functional role. Two types of variability are described: `strategic shot selection` and `movement variability`. In `strategic shot selection`, the outcome remains consistent, but the swing kinematics/kinetics (resulting in the desired ball flight) are free to vary; `movement variability` is the changes in swing kinematics and kinetics from trial to trial when the golfer attempts to hit the same shot. These changes will emerge due to constraints of the golfer's body, the environment, and the task. Biomechanical research has focused upon aspects of technique such as elite versus non-elite kinematics, kinetics, kinematic sequencing, peak angular velocities of body segments, wrist function, ground reaction forces, and electromyography, mainly in the search for greater distance and clubhead velocity. To date very little is known about the impact of variability on this complex motor skill, and it has yet to be fully researched to determine where the trade-off between functional and detrimental variability lies when in pursuit of enhanced performance outcomes.